Dual Versus Mono Antiplatelet Therapy in Large Atherosclerotic Stroke: A Retrospective Analysis of the Nationwide Multicenter Stroke Registry. Issue 5 (May 2019) - Kim, Dohoung; Park, Jong-Moo; Kang, Kyusik; Cho, Yong-Jin; Hong, Keun-Sik; Lee, Kyung Bok; Park, Tai Hwan; Lee, Soo Joo; Kim, Jae Guk; Han, Moon-Ku; Kim, Beom Joon; Lee, Jun; et al.
Abstract : Background and Purpose—: Two large-scale randomized controlled trials of recurrent stroke prevention suggest that dual antiplatelet therapy with clopidogrel plus aspirin is beneficial for prevention of subsequent ischemic events. There is a paucity of data, however, on the efficacy or effectiveness of such an approach in the treatment of stroke patients with symptomatic large artery atherosclerotic occlusive disease. Methods—: We used a multicenter stroke registry database (Clinical Research Collaboration for Stroke in Korea) to analyze acute ischemic stroke patients due to large artery atherosclerotic occlusive disease who were treated with aspirin alone or combination of clopidogrel and aspirin from May 2008 to May 2015. The results were analyzed by intention-to-treat, per-protocol, and as-treated methodologies. The primary end point was the 1-year composite outcome of stroke recurrence, myocardial infarction, and all-cause death. To balance the differences between groups, a frailty model using propensity scores and inverse probability of treatment weighting was used. Results—: A total of 5934 patients with symptomatic large artery atherosclerotic occlusive disease were treated either with clopidogrel plus aspirin (n=2903, 49%) or aspirin (n=3031, 51%). The frequency of the primary outcome was 12% (n=353) in the clopidogrel-aspirin group and 14% (n=410) in the aspirin group. The hazards of the primary outcome with combination over aspirin only were significantly reduced in the per-protocol and as-treated analyses (hazard ratio, 0.71; 95% CI, 0.57–0.88; P =0.002 and hazard ratio, 0.81; 95% CI, 0.69–0.96; P =0.02, respectively), but there was borderline significance in the intention-to-treat analysis (hazard ratio, 0.86; 95% CI, 0.74–1.01; P =0.06). Combination therapy was beneficial for all-cause death in all analyses but did not reduce recurrent stroke. Conclusions—: Compared with patients receiving aspirin monotherapy, the primary outcome seemed to occur less frequently in patients receiving dual antiplatelet therapy, which is explained mainly by the decrease of all-cause death. Since this is a nonrandomized, retrospective, observational study, our study should be cautiously interpreted. Abstract : Supplemental Digital Content is available in the text.